2023
DOI: 10.17159/2411-9717/1508/2023
|View full text |Cite
|
Sign up to set email alerts
|

Material characteristics of Ti-6AL-4V samples additively manufactured using laser-based direct energy deposition

Abstract: Although additive manufacturing is fast gaining traction in the industrial world as a reputable manufacturing technique to complement traditional mechanical machining, it still has problems such as porosity and residual stresses in components that give rise to cracking, distortion, and delamination, which are important issues to resolve in structural load-bearing applications. This research project focused on the characterization of the evolution of residual stresses in Ti-6Al-4V extra-low interstitial (ELI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The hardness at the top region of the peened samples was observed to be higher than that of the core and lower regions of the samples, thus confirming the top region to exhibit more compressive stresses, while the core and lower regions of the specimens showed more tensile stresses. This compares well with the literature by Arthur et al [51], which reported lower hardness values for the greater tensile stress regions of samples, which were analysed for stress magnitudes by using neutron diffraction, while higher hardness was reported for the greater compressive stress regions of the DED-fabricated Ti-6Al-4V samples. Since LSP generates shock waves, the hardness is expected to decrease with depth within the sample for treated sections as compared to untreated sections.…”
Section: Influence Of Laser Peening On Electrochemical Responsesupporting
confidence: 90%
“…The hardness at the top region of the peened samples was observed to be higher than that of the core and lower regions of the samples, thus confirming the top region to exhibit more compressive stresses, while the core and lower regions of the specimens showed more tensile stresses. This compares well with the literature by Arthur et al [51], which reported lower hardness values for the greater tensile stress regions of samples, which were analysed for stress magnitudes by using neutron diffraction, while higher hardness was reported for the greater compressive stress regions of the DED-fabricated Ti-6Al-4V samples. Since LSP generates shock waves, the hardness is expected to decrease with depth within the sample for treated sections as compared to untreated sections.…”
Section: Influence Of Laser Peening On Electrochemical Responsesupporting
confidence: 90%